Insecticide use, farmers’ self-reported health status, and genetically modified cowpea in Nigeria: Findings from a clustered randomized controlled trial with causal - Amare, Mulubrhan; Andam, Kwaw S.; Spielman, David J.; Bamiwuye, Temilolu; Nwagboso, Chibuzo; Zambrano, Patricia; Chambers, Judith A. (International Food Policy Research Institute, 2025)
Excessive insecticide use in smallholder agriculture can threaten human health and the environment. We evaluate the effects of receiving a genetically modified cowpea variety that confers resistance to the legume pod borer (Maruca vitrata) using a clustered randomized controlled trial with an encouragement design in Nigeria. We find that farmers who received the pod borer-resistant (PBR) cowpea with complementary inputs significantly reduce insecticide volumes and report fewer days of insecticide-related illness compared to farmers who only received a conventional cowpea variety. Farmers receiving PBR cowpea alone experience smaller, mostly insignificant reductions. To explore heterogeneous responses, we combine ANCOVA (analysis of covariance) interactions with machine learning-based Causal Forest estimates of Conditional Average Treatment Effects (CATEs). Results reveal that smaller, less wealthy, and labor-constrained households experience the largest reductions in insecticide use and health improvements, whereas wealthier farmers or those with higher baseline spraying practices experience lower reductions. Women-managed plots exhibit modestly higher responsiveness. Our findings highlight the importance of moving beyond average effects and seed distribution toward targeted, context-specific interventions that account for behavioral and resource constraints in smallholder farming systems.